2007
DOI: 10.1097/sla.0b013e3181492c28
|View full text |Cite
|
Sign up to set email alerts
|

External Drainage of Pancreatic Duct With a Stent to Reduce Leakage Rate of Pancreaticojejunostomy After Pancreaticoduodenectomy

Abstract: External drainage of pancreatic duct with a stent reduced leakage rate of pancreaticojejunostomy after pancreaticoduodenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
264
2
7

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 358 publications
(279 citation statements)
references
References 40 publications
6
264
2
7
Order By: Relevance
“…All four trials reported on the incidence of POPF formation following PD with versus without external pancreatic duct stent placement [6][7]9,14]. There was a statistically significant difference in the overall incidence of any grade POPF formation among these cohorts (OR 0.37, 95% CI=0.23 to 0.58, P=0.0001) as well as a statistically significant difference in the incidence of clinically significant (grade B or C) POPF (OR 0.50, 95% CI=0.30 to 0.84, P=0.0009) favoring external stent placement (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All four trials reported on the incidence of POPF formation following PD with versus without external pancreatic duct stent placement [6][7]9,14]. There was a statistically significant difference in the overall incidence of any grade POPF formation among these cohorts (OR 0.37, 95% CI=0.23 to 0.58, P=0.0001) as well as a statistically significant difference in the incidence of clinically significant (grade B or C) POPF (OR 0.50, 95% CI=0.30 to 0.84, P=0.0009) favoring external stent placement (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent screening resulted in four prospective randomized trials examining only external pancreatic stents following PD [6][7]9,14]. Of note, the present study excluded two trials previously included by Markar et al [10]; 1) the 2009 prospective trial conducted by Smyrniotis et al [5] on the basis that this study examined internal stents only, and 2) the 2006 trial conducted by Winter et al [4] on the basis that internal stents were included and because these authors utilized an alternating method of allocating patients to either treatment or control arms, which may have inadvertently introduced selection bias as described by Doll [15].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pancreatic stenting through pancreatic anastomosis after PDT has long been reported by many authors (1,24,29,42) . Some reasons supporting the usefulness of an internal stent are diverting the pancreatic enzymes from the pancreatic anastomotic area and to allow more precise placement of sutures during pancreatic anastomosis.…”
Section: Pancreatic Fistulamentioning
confidence: 99%